Netherlands yearbook of international law. Volume 46, 2015. Jus cogens : Quo vadis? - Heijer, Maarten den; Wilt, Harmen van der, 1955- (The Hague : Berlin : Asser Press ; Springer, 2016)
Jus cogens is a formidable yet elusive concept of international law. Since its incorporation in the Vienna Convention on the Law of Treaties some 35 years ago, it has made tentative inroads into international legal practice. But its role in international law is arguably less prominent than might have been expected on the basis of its powerful potential and in view of wider developments in international law that call for constitutionalisation and hierarchy, including the processes of fragmentation and humanization. This volume of the 'Netherlands Yearbook of International Law' sets out to clarify the concepts and doctrines relevant to jus cogens and to sharpen the debate on its theoretical foundations, functions and legal effects. To that purpose, the volume brings together contributions on the genesis and function of jus cogens, on the application of jus cogens in specialised areas of international law and on its enforcement and legal consequences. Together, they reinforce the understanding of jus cogens as a hierarchical concept of international law and shed light on its potential for further development.
Includes bibliographical references and index.
Keywords: Jus cogens (International law); International law; Law / International; International law; Jus cogens (International law)